Pengembangan Panduan Praktikum Kultur Jaringan dalam Pembelajaran Biologi di SMA Kristen Makedonia - Nuraini, Debora; Astuti, Indri; Enawaty, Eny (Jurnal Biotek, 2022)
This study was based on the finding that students were frequently found to be active but not systematic or following practicum procedures during the biology practicum. The purpose of this research was to develop a practicum guide sheet. This study used the ADDIE model for research and development (R&D), so in the data collection technique, the researcher used a questionnaire. Three experts in design, media, and materials were involved in this study during the odd-numbered August semester, and nine students participated in small-scale trials. The research instrument was a questionnaire, and the data collected was analyzed qualitatively and descriptively quantitatively. The results of the research from expert validation showed that according to material experts, the percentage of eligibility is 98%, media experts are 98%, and design experts are 100%. Whereas in small-scale implementation, the eligibility of the product assessed by students was 94%, namely "very feasible." Based on the existing findings, it can be concluded that the development of practicum guidelines needs to be done in biology learning at Christian Macedonian High Schools. This research has implications for improving the biology learning process and can be used as a resource for other writers.